Audiometric Findings in Patients with Age Related Hearing Loss - Ahmed, Farhan; Jawad, Ayesha; Ahmad Umar, Mumtaz; Iftikhar, Saira; Akhtar, Aimen; Rabbani, M Zafar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the audiometric findings, prevalence of age related hearing loss and association of hearing loss with gender in patients of 60 years and above. Setting and duration of study: This study was conducted in the Department of ENT at Shifa Foundation Community Health Centre (SFCHC), Shifa International hospital, Islamabad, over a period of 5 years from September 2014 to September 2019. Methods: A total of 149 patients were included in the study. All the patients were subjected to audiometry after taking informed written consent. Information regarding the past medical history of all participants regarding ear and hearing disorders and risk factors was taken and recorded. All this information along with demographic information was recorded. Results: The mean age of the participants was 70.72 ± 7.09 years. Most 46 (30.9%) of the patients were between 60 to 65 years old. The proportion of male participants 76 (51%) was slightly higher. In our study sample, 142 (95.3%) of the participants had high-frequency hearing loss, and 129 (86.6%) participants had low-frequency hearing loss. Mostly 62 (41.6%) participants had sloping curve. Most 125 (83.9%) participants were diagnosed with both types of hearing loss. Among male patients flat curve showed a significant (P-value < 0.05) relationship with age and in female patients, flat curve and neither flat curve nor sloping curve showed significant (P-value < 0.05) association with different age brackets. Conclusion: High-frequency hearing loss was the most common type of hearing loss among older patients. Majority of the patients were diagnosed with both types of hearing loss. High-frequency hearing loss was found to be significantly associated with different age brackets.